Communication for development. Towards effective communication - Soliman, Mona Ali (AUC Knowledge Fountain, 2018)
The purpose of this study is to understand and identify the success factors of Communication for Development endeavors. By understanding the past efforts and studying the current methodologies used in the different phases of campaigns this study aims to conceptualize the most effective ways to generate Communication for Development products. Through the examination of foreign and local case studies in this research paper, it is anticipated to have a clear conceptualization of what makes some development campaigns succeed, in terms of message design and outreach rather than others. Meanwhile, through the expert interviews, this study aims to understand the process that marketing professionals take in order to design messages for Communication for Development. Finally, this paper strives to have a better understanding of how marketing professionals plan, design, execute and evaluate Communication for Development campaigns.